2016
DOI: 10.1038/cr.2016.45
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of PXY-TDIF complex reveals a conserved recognition mechanism among CLE peptide-receptor pairs

Abstract: Plants can achieve amazing lifespans because of their continuous and repetitive formation of new organs by stem cells present within meristems. The balance between proliferation and differentiation of meristem cells is largely regulated by the CLAVATA3/ENDOSPERM SURROUNDING REGION (CLE) peptide hormones. One of the well-characterized CLE peptides, CLE41/TDIF (tracheary elements differentiation inhibitory factor), functions to suppress tracheary element differentiation and promote procambial cell proliferation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
132
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(147 citation statements)
references
References 42 publications
13
132
1
1
Order By: Relevance
“…Given the conserved C-termini of AtPep1, TDIF and RGF1, and the conserved RxR motif of AtPEPR1 and RGFRs, RGFRs might also use SERK members as co-receptors. This hypothesis is consistent with the observation that SERK members play critical but brassinosteroid-independent roles in root meristem activities [28]. Gel-filtration results showed that RGF1 induced the interaction between RGFR1 LRR or RGFR2 LRR and SERK1/2/BAK1 LRR ( Figure 5A, 5B and Supplementary information, Figure S12), further strengthening our conclusion that RGFRs 1 and 2 function as receptors of RGF1.…”
Section: Serk Family Members As Co-receptors With Rgfssupporting
confidence: 79%
“…Given the conserved C-termini of AtPep1, TDIF and RGF1, and the conserved RxR motif of AtPEPR1 and RGFRs, RGFRs might also use SERK members as co-receptors. This hypothesis is consistent with the observation that SERK members play critical but brassinosteroid-independent roles in root meristem activities [28]. Gel-filtration results showed that RGF1 induced the interaction between RGFR1 LRR or RGFR2 LRR and SERK1/2/BAK1 LRR ( Figure 5A, 5B and Supplementary information, Figure S12), further strengthening our conclusion that RGFRs 1 and 2 function as receptors of RGF1.…”
Section: Serk Family Members As Co-receptors With Rgfssupporting
confidence: 79%
“…RPK2 contains two island domains that map to the N-terminal and central portions of its LRR domain, but their function is unknown (63,106,114). By contrast, most of the characterized peptide ligand LRR-RKs, such as HAESA, TDR/PXY, FLS2, and PEPR, do not contain island-domain structures (89,100,120,122,144). This suggests that plants may have evolved island-domain-containing LRR ectodomains to facilitate the specific binding of relatively small ligands.…”
Section: C)mentioning
confidence: 96%
“…In this case, however, the N-terminal capping domain of SERK1 binds on top of the IDA binding groove in HAESA, forming a lid structure that covers the three C-terminal amino acids in IDA (Figure 8a,b). These amino acids are conserved among the different IDLs and are also found in other plant peptide hormones, suggesting that these peptides also require co-receptor kinases for receptor activation (100,115,122,144) (Figure 7e). In the case of HAESA, the contribution of the SERK1 ectodomain to IDA binding has been quantitatively assessed: In the absence of the co-receptor, HAESA binds IDA with micromolar affinity, whereas SERK1 shows no detectable binding to the peptide hormone.…”
Section: Leucine-rich-repeat Receptor Kinase Activation By Shape-compmentioning
confidence: 99%
See 2 more Smart Citations